2009
DOI: 10.1542/peds.2008-3743
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Disability Through 11 Years of Age in Children Born Before 26 Weeks of Gestation

Abstract: Extremely preterm children remain at high risk for neurodevelopmental disability at 11 years of age compared with term peers. The prevalence of disability remained stable between 6 and 11 years of age, and large individual shifts in classification of disability were unusual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
206
3
13

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 244 publications
(232 citation statements)
references
References 29 publications
10
206
3
13
Order By: Relevance
“…Follow-up studies have shown that these children are often confronted with developmental problems and psychiatric diagnoses in late childhood and early adolescence (2)(3)(4)(5)(6)(7)(8)(9). Studies also suggest a link between extreme prematurity and autism spectrum disorder (ASD), characterised by persistent deficits in social communication and social interaction, and restrictive and repetitive patterns of behaviours, interests or activities (10).…”
Section: Introductionmentioning
confidence: 99%
“…Follow-up studies have shown that these children are often confronted with developmental problems and psychiatric diagnoses in late childhood and early adolescence (2)(3)(4)(5)(6)(7)(8)(9). Studies also suggest a link between extreme prematurity and autism spectrum disorder (ASD), characterised by persistent deficits in social communication and social interaction, and restrictive and repetitive patterns of behaviours, interests or activities (10).…”
Section: Introductionmentioning
confidence: 99%
“…These comprised two cohorts of children from the EPICure Study, [13][14][15] a longitudinal epidemiological study of outcome following extremely preterm birth in the UK and Ireland (http://www.epicure.ac.uk). The first group comprised a national cohort of all infants who were born extremely preterm (£25wks' gestation) in the whole of the UK and Ireland from 1 March to 31 December 1995.…”
Section: Methods Participantsmentioning
confidence: 99%
“…(Descriptions of these cohorts have been published previously. [13][14][15] ) Parents and children received study information leaflets and parents provided informed consent for their child's participation at both 6 and 11 years. …”
mentioning
confidence: 99%
“…Studies have characterized the peculiarities of preterm infant development (1)(2)(3) as complications suffered early (7)(8) , and at later ages (9)(10)(11)(12) , showing losses or damages in various dimensions. However, they have focused the assessment of deficits on abilities and behaviors in specific areas such as speech, motor function, or school learning through standardized tests.…”
Section: Introductionmentioning
confidence: 99%